PENERAPAN PROJECT BASED LEARNING (PjBL) DALAM MENINGKATKAN MAHĀRAH QIRĀAH PADA KURIKULUM MERDEKA BELAJAR - Salsabila, Novita Maula; Setiyawan, Agung (STIQ Amuntai, 2024)
The competitive environment and increasingly competitive global issues necessitate competency development that satisfies 21st-century demands. The Free Learning Curriculum is a response effort in addressing it. Project Based Learning (PjBL) is a viable and effective approach when implementing the Free Learning Curriculum. With the use of Project-based Learning (PjBL) in the Independent Learning Curriculum, this study attempts to investigate the factors that help and hinder learning Arabic. The research methodology for the library research uses a qualitative descriptive approach. By gathering material from numerous pertinent sources, including books, articles, and journals pertaining to the research topic, data were acquired through documentation approaches. The three steps of the data analysis technique are reduction, data display, and conclusion drawing. The study's findings demonstrate that using PjBL to learn Arabic has a beneficial effect on the growth of analytical critical thinking abilities as well as creativity, teamwork, and communication in everyday situations. This discovery aligns with the goals of the Free Learning Curriculum, which aims to offer relevant projects that facilitate an engaged, relevant, and meaningful learning experience. PjBL implementation is aided by the growth of language skills, contextual learning, student collaboration, and skills-based methodologies. However, there are hurdles for students who have not acquired Arabic language skills yet are expected to engage actively, as well as time constraints, resource limitations, disparities in assessment, and other issues. When PjBL is used to learn Arabic, students can maximise their Arabic language competence and enhance their speaking skills to a great extent.